The use of SCL-k-9 to measure general psychopathology in women and men with skin conditions - Samela, Tonia; Cordella, Giorgia; Antinone, Valeria; Sarandrea, Paride; Giampetruzzi, Anna Rita; Abeni, Damiano (Frontiers in Psychology, 2022)
Objectives: To measure general psychopathology in dermatologic outpatients using the Symptom-Checklist-K-9 (SCL-K-9); to investigate whether the SCL-K-9 is able to categorize patients with and without significant non-psychotic disorders; and to perform a single-item analysis of the SCL-K-9, with a focus on gender differences. Methods: Cross-sectional study on consecutive dermatological patients. We used two self-administered questionnaires to assess general psychopathology symptoms: General Health Questionnaire-12 (GHQ-12) and SCL-K-9. Sociodemographic information was collected with standardized forms. The performance of the SCL-K-9 in classifying patients according to their current emotional distress severity, was assessed using a ROC procedure. Finally, we measured differences in scores obtained among women and men in SCL-K-9 single items. Results: A total of 292 patients were studied (71.2% women). We observed statistically significant differences in SCL-K-9 total mean scores among genders (0.88, for women vs 0.56 for men; p<0.001) and among most single items. We found that it would be more appropriate to use gender-specific cut-offs when using SCL-K-9 to screen dermatological patients for general psychopathology. Conclusion: The SCL-K-9, with its compact format could provide, in a short time, a wider range of information related to critical areas that challenge the mental health of patients with skin diseases.